Nonlinear Properties of PMMA Composite Thin Films - Clavian L M; Rajesh Kumar P C; Anil Kumar K. V; Narayana Rao D; Shihab N K; Ganesh Sanjeev (Science and Technology - Recent Updates and Future Prospects Vol. 5, 2024)
The optical properties of thin films composed of TPP-infused PMMA were investigated using the z-scan technique. These films, ranging in thickness from 200 to 400 nm, were prepared using spin-coating. Despite varying concentrations of TPP in the PMMA matrix, the UV-visible absorption spectrum displayed no shifts in absorption wavelength. However, the composite films demonstrated robust nonlinear absorption (NLA) and nonlinear refraction (NLR) coefficients, ranging from 10-6 to 10-5 m/W and 10-13 to 10-12 m2/W, respectively. Notably, the third-order nonlinear susceptibility, \(χ\)(3), increased with higher TPP concentrations. These findings suggest the potential of these TPP-incorporated PMMA spin-coated thin films for the fabrication of nonlinear optical devices.